CHARACTER EDUCATION BASED ON RELIGION AND NATION CULTURE - Ari Kurniawati (Jurnal Ilmiah Pesantren, 2018)
Character education in Indonesia has become a necessity. Various cases of crime and moral deviations become evident that the character of most citizens already at alarming stage. Therefore character education is absolutely necessary not only in school, but also at home and in other social environments. Due to the facts character education is proclaimed in all the levels of education. Character education becomes the core of national education, to have faith fear to Allah and noble. Character education at its core aims to form a nation that is strong, competitive, moral, tolerant and dynamic science oriented by faith to God almighty based on Pancasila.The character education can be implemented through some strategies, namely by inclusive strategy from the teacher, school culture strategy, self exploration strategies and by peer group evaluationCharacter education